THE USE OF THE FUNGUS Metarhizium rileyi F. IN THE CONTROL OF Crocidolomia pavonana F. ON CABBAGE (Brassica oleracea L.) - Stella Priscilia Manguande; Max M. Ratulangi; Vivi B. Montong; Selvie Tumbelaka (Sam Ratulangi University, 2021)
This study aims to determine the effect of M. rileyi F. fungus with various concentrations on the mortality of C. pavonana F. pests on cabbage plants in the laboratory and to find out how the effect of M. rileyi F. fungus on C. pavonana F. pests. This research was conducted from September to November 2020, at the BPTPH Laboratory (Center for the Protection of Food Crops and Horticulture) and the method used in this study was a Completely Randomized Design (CRD), which consisted of five treatments namely Control (A), 109 ( B), 108 (C), 107 (D), and 106 (E) and each treatment was repeated three times. The collection of C. pavonana F. larvae was carried out on cabbage plantations in Tomohon City. The larvae used as research test materials are third instar larvae. The results of the data obtained in the study were analyzed using analysis of variance and if the treatment showed a significant effect, it would be continued with the Least Significant Difference (BNT) test. The results of the study, M. rileyi F. proved effective to kill C. pavonana F. larvae from several treatments with different concentrations found the average with the highest value at treatment concentration of 109 was 54.28%. While the lower values, respectively, were found in the treatment concentrations of 108 , 107 , and 106 with values of 35.23%, 27.61%, 21.90% respectively. Keywords: Control; Fungus; Cabbage Plant; Pest; Metarhizium rileyiAbstrakPenelitian ini dilaksanakan pada bulan September sampai November 2020, bertempat di Laboratorium BPTPH (Balai Perlindugan Tanaman Pangan dan Hortikultura) dan metode yang digunakan dalam penelitian ini adalah Rancangan Acak Lengkap (RAL), yang terdiri dari lima perlakuan yakni Kontrol (A), 109 (B), 108 (C), 107 (D), dan 106 (E). dan masing-masing perlakuan diulangi sebanyak tiga kali. Pengambilan larva C. pavonana F. dilakukan pada lahan pertanaman kubis di Kota Tomohon. Larva yang digunakan sebagai bahan uji penelitian merupakan larva instar tiga. Hasil dari data yang diperoleh dalam penelitian dianalisis menggunakan analisis sidik ragam dan apabila perlakuan menunjukkan pengaruh yang nyata akan dilanjutkan dengan uji Beda Nyata Terkecil (BNT). Hasil dari penelitian, jamur M. rileyi F. terbukti efektif untuk membunuh larva C. pavonana F. dari beberapa perlakuan dengan konsentrasi yang berbeda ditemukan rataan dengan nilai tertinggi pada perlakuan konsentrasi 109 sebesar 54,28%. Sedangkan nilai yang lebih rendah secara berurutan terdapat pada perlakuan konsentrasi 108 , 107 , dan 106 yakni dengan nilai masing – masing sebesar 35,23%, 27,61%, 21,90%.Kata Kunci: Pengendalian; Jamur; Tanaman Kubis; Hama; Metarhizium rileyi